A new species of Eocene fossil Malthodes (Coleoptera: Cantharidae) with a rarely observed aedeagus - Fanti, Fabrizio; Pankowski, Madeline V. (Zootaxa, 2024)
A new Malthodes (Coleoptera, Cantharidae, Malthininae) in Eocene amber from Poland (Baltic amber) is illustrated and described here: Malthodes (s. str.) maximiliani sp. nov. The new species of soldier beetle is characterized by its small body size and last tergites and last sternite distinct from similar taxa. Notably, the specimen has a partially visible aedeagus, a characteristic rarely seen in fossil Malthodes of the nominotypical subgenus; it has been observed in only three fossil species of this subgenus.